Vengeance is Mine: A Model of Emotional Appraisal and Computer Abuse - Kim, J.; Park, E.; Baskerville, Richard (IFIP, 2012)
What factors drive individuals to abuse information systems? Better understanding of the roots behind this individual decision could provide opportunities to reduce computer abuse by reducing the presence of these factors. In this paper, we examine the effects of both organizational and personal factors on an individual’s computer abuse behavior. We develop our theoretical model based on abuse opportunity structure theory and literature on emotion theory. Specifically, we identify the organization abuse structure as an organizational factor and three personal factors (goal conduciveness, abuse positive affect, and morality) as personal factors. We investigate their effects on the assessments and decisions that individuals make about computer abuse. The results of a controlled laboratory experiment showed that the organization abuse structure affects these decisions through the assessment of goal conduciveness and abuse positive affect. Morality, however, was found to directly and indirectly affect an individual’s abuse intent. These results imply that security practices are subject to individual appraisals that raise emotions that are in turn conditioned by morality in specific ways. A technical evaluation of the practices is incomplete when absent of the individual appraisal.